Assessment of operational models in the Balearic Sea during a MEDESS-4MS experiment. (November 2016) - Capó, E.; Orfila, A.; Sayol, J.M.; Juza, M.; Sotillo, M.G.; Conti, D.; Simarro, G.; Mourre, B.; Gómez-Pujol, L.; Tintoré, J.
Abstract: We study the capabilities of four existing Operational Forecasting Systems to forecast the trajectories of a hypothetical surface oil spill in a region of the Western Mediterranean Sea, the Balearic sub-basin. Two of the systems operate at basin scale (MyO-GLOBAL and MED-MFC) and the other two at regional scale (IBI-MFC and WMOP). The model assessment is first studied using synoptic fields of models and observations from ship in two different areas. The behavior of all systems shows similarities and differences with the real observations especially within the thermocline. Secondly, a Lagrangian assessment points out the large differences obtained between the different models in the different areas. Results indicate the importance of reproducing the sub-mesoscalar structures in the Balearic Sea in order to develop accurate and reliable tracking systems, a question that today is far from being achieved.